Badanie sprawozdania finansowego jednoosobowej spółki Skarbu Państwa w świetle wytycznych ministra Skarbu Państwa w obszarze nadzoru właścicielskiego - Bogacz-Miętka, Olga (Examination of Financial Statements in Sole Shareholder Company of the Treasury in the Light of Guidelines of Minister of Treasury in the Scope of Corporate Governance, 2007)
In Poland, in spite of numerous privatisation processes, the state sector still presents considerable part of the market. State-Owned Enterprises are mainly prevalent in utilities and infrastructure industries, such as energy, transport and telecommunication, which performance is of great importance to broad segments of the population and to other parts of the business sector. Among the companies with Treasury involvement, in terms of capital, there is a lot of Sole Shareholder Companies of the Treasury. Under regulations of statutes of all Sole Shareholder Companies of the Treasury, their financial statements are subject to examination by impartial and independent certified auditor. The aim of this paper is to present the procedure of examination of financial statements of Sole Shareholder Company of the Treasury and principles for co-operation of the supervisory board with the auditor, in accordance with the guidelines of the Ministry of the Treasury as a representative of the Treasury in the process of exercising ownership supervision over these companies. Effective cooperation of the supervisory board with the auditor should contribute to the early detection of anomaly in the function of the company's finance system, state property mismanagement and acting to the detriment of entities with Treasury, which were confirmed on numerous occasions by reports elaborated by the Supreme Chamber of Control, parliamentary inquiries and newspaper stories. The paper also presents the international guidelines of Organisation for Economic Co-operation and Development (OECD), in the scope of examination of financial statements in companies with Treasury shareholding.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 183-195